Computer experiences, self-efficacy and attitude towards computer use: a study among distance teaching students, university of Ibadan, Nigeria. (2009)
This study investigated Computer experience, Computer self-efficacy and attitude of Distance Learning students toward Computer use in University of Ibadan, Nigeria. 250 part-time students in the Department of Library, Archival and Information Studies (LARIS), Faculty of Education, were randomly sampled to take part in the study. Questionnaire was used to elicit information on the three research variables. The findings revealed that the Computer experience of the undergraduates correlate positively with their attitude towards the use of computer(r=0.35;p<0.01).It was also revealed that a positive relationship exists between Computer self-efficacy and attitude of students toward the use of computer(r=0.39;p<0.01).The two Computer - related variables were also found to have significant composite effect on attitude of the part-time students toward the use of Computer(R=0.509;p<0.01). The study recommends the integration of Computer courses into the curriculum at all levels of education (primary, secondary and tertiary). It also recommends provision of Computer laboratories equipped with internet facilities in the library and the faculties for students’ use.